Bioinspired thermally conducting packaging for heat management of high performance electronic chips - Huawei Wang; Pengfei Bai; He Cui; Xiaotong Zhang; Yifan Tang; Shaoyu Liang; Shixiao Li; Guofu Zhou (Communications Engineering)
Abstract Conventional electronic chip packaging generates a huge thermal resistance due to the low thermal conductivity of the packaging materials that separate chip dies and coolant. Here we propose and fabricate a closed high-conducting heat chip package based on passive phase change, using silicon carbide which is physically and structurally compatible with chip die materials. Our “chip on vapor chamber” (CoVC) concept realizes rapid diffusion of hot spots, and eliminates the high energy consumption of refrigeration ordinarily required for heat management. Multi-scale wicks and bionic vein structures are applied to CoVC leading to an increase of 164% in heat transfer performance. The thermal resistance of the package was only a third that of traditional packaging systems. This means that the structure of CoVC has a good thermal conducting ability and can reduce energy consumption for heat dissipation.